Motivational orientations and learning strategies among undergraduate students in study circle course - Syam, Sri Rahmayana; Nik Abdullah, Nik Md. Saiful Azizi; Badrasawi, Kamal J I (Canadian Center of Science and Education, 2016)
In line with the vision and mission of the International Islamic University Malaysia, the study circle (halaqah) course is designed to improve undergraduate students in all aspects (intellectual, moral, spiritual, social, and physical) as well as develop their communication and critical thinking skills. Learning motivation and learning strategies are essential to achieve the desired learning outcomes of the course. Thus, this research aims to assess the students’ perception on their learning motivational orientations (i.e., self-efficacy and task performance and task value) and learning strategies (i.e., elaboration and peer learning). This research employed the quantitative approach in which a survey design method was used. A sample of 329 undergraduate students randomly selected form the students registered in study circle (halaqah) course were asked to complete sub-scales adopted from the Motivated Strategies for Learning Questionnaire (MSLQ). Descriptive statistics using mean scores and standard deviations, t-test and Pearson product-moment correlation coefficient were used in the data analysis. The students, regardless of gender, showed high level of learning motivational orientations in taking the study circle in terms of interest, importance and utility. They were motivated and confident to understand and perform the study circle tasks. Elaboration and peer learning strategies were used to perform such tasks. There was also a large positive relation between learning motivational orientations and learning strategies of motivational orientations. Further qualitative and quantitative researches were recommended to get more in depth information.